Modulating Microglial Cells for Promoting Brain Recovery and Repair - Hermann, Dirk M.; Gunzer, Matthias (Frontiers in Cellular Neuroscience, 2021)
Representing the brain’s innate immune cells that interact vividly with blood-derived immune cells and brain parenchymal cells, microglia set the stage for successful brain remodelling and repair in the aftermath of brain damage. With the development of pharmacological colony stimulating factor-1 receptor inhibitors, which allow inhibiting or depleting microglial cells, and of transgenic mice allowing the inducible depletion of microglial cells, experimental tools have become available for studying roles of microglia in neurodegenerative and neurorestorative processes. These models open fundamental insights into roles of microglia in controlling synaptic plasticity in the healthy and the injured brain. Acting as a switch from injury to repair, microglial cells might open opportunities for promoting neurological recovery in human patients upon brain injury.